PENGARUH PENDIDIKAN, PENGALAMAN, DAN FAKTOR SOSIAL TERHADAP PEMANFAATAN INFORMASI LAPORAN ARUS KAS (Studi Empiris pada Instansi Pemerintah di Jawa Tengah) - Winda Rosiana Pratiwi; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the influence of education, experience, and social factors to use of information  of Cash Flow Statement. To full fill of  information needs for the user, the government provide financial statement as a planning, controling, and decision making. The user quality affect to the usefull of information in financial statements required.The population  on this study were the leader, supervisors, and inspectors as the financial statement user to make economic decisions. The scope of the study refers to Central Java government  and respondents function (position), so this study do with questioner as a means of collecting primary data. Likert scale of measurement used. Regression model used to analized all variable of this hypothesis.The results showed that education, experience, and social factors has positive and a significant effect to the usefull of information of cash flow statement to Central Java government.